Analysis of Performance Metrics of Semantic Communication Systems - JIANG Sheng-teng, ZHANG Yi-chi, LUO Peng, LIU Yue-ling, CAO Kuo, ZHAO Hai-tao, WEI Ji-bo (Jisuanji kexue, 2022)
Semantic communication system is currently a hot research topic in the communication field,but a mature evaluation system has not been established in this field,which leads to the different performance of semantic communication systems designed under different performance metrics.This paper mainly focuses on semantic communication systems,introducing perfor-mance metrics based on precision,performance metrics based on recall,performance metrics based on the combination of precision and recall,and performance metrics based on word vector space models.It also elaborates on the background,significance,main algorithm ideas,and scope of application of various performance metrics in semantic communication,and analyzes and compares the differences,advantages and disadvantages of each performance metric.Finally,it summarizes the problems faced by semantic communication performance metrics at this stage,and points out the future development direction of performance metrics research in semantic communication system.